Inhibition of mouse breast adenocarcinoma growth by ablation with intratumoral alpha-irradiation combined with inhibitors of immunosuppression and CpG - Confino, Hila; Umansky, Viktor (Cancer immunology immunotherapy, 2016)
It has been demonstrated that aggressive in situ tumor destruction (ablation) could lead to the release of tumor antigens, which can stimulate anti-tumor immune responses. We developed an innovative method of tumor ablation based on intratumoral alpha-irradiation, diffusing alpha-emitters radiation therapy (DaRT), which efficiently ablates local tumors and enhances anti-tumor immunity. In this study, we investigated the anti-tumor potency of a treatment strategy, which combines DaRT tumor ablation with two approaches for the enhancement of anti-tumor reactivity: (1) neutralization of immunosuppressive cells such as regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) and (2) boost the immune response by the immunoadjuvant CpG. Mice bearing DA3 mammary adenocarcinoma with metastases were treated with DaRT wires in combination with a MDSC inhibitor (sildenafil), Treg inhibitor (cyclophosphamide at low dose), and the immunostimulant, CpG. Combination of all four therapies led to a complete rejection of primary tumors (in 3 out of 20 tumor-bearing mice) and to the elimination of lung metastases. The treatment with DaRT and Treg or MDSC inhibitors (without CpG) also resulted in a significant reduction in tumor size, reduced the lung metastatic burden, and extended survival compared to the corresponding controls. We suggest that the therapy with DaRT combined with the inhibition of immunosuppressive cells and CpG reinforced both local and systemic anti-tumor immune responses and displayed a significant anti-tumor effect in tumor-bearing mice.
Gesehen am 04.07.2019